KUALITAS PELAYANAN PUBLIK PADA KANTOR CAMAT TENAYAN RAYA KOTA PEKANBARU - astuti, widia; irawati, irawati; ruslihardy, ruslihardy (Jurnal Niara, 2016)
The success of regional development by the government run by these areas, where the implementation is greatly influenced by the ability of the apparatus in performing their duties. The role of the government apparatus is mostly used as a means of renewal and empowerment of the community. Therefore, the basic functions and control performed by the government apparatus is the formulation and implementation of policies that function as a motivator and facilitator for the achievement of fair and equitable development goals in all fields. Conservation of one of the spearheads of public services must provide optimal service and quality sehinggah the role of kecamatan as a salag of one community service can be efficient and effective.